2020
DOI: 10.1021/jacs.0c02275
|View full text |Cite
|
Sign up to set email alerts
|

Host-Enhanced Phenyl-Perfluorophenyl Polar−π Interactions

Abstract: Phenyl-perfluorophenyl polar−π interactions have been revisited for the design and fabrication of functional supramolecular systems. The relatively weak associative interactions (ΔG ≈ −1.0 kcal/mol) have limited their use in aqueous selfassembly to date. Herein, we propose a strategy to strengthen phenyl-perfluorophenyl polar−π interactions by encapsulation within a synthetic host, thus increasing the binding affinity to ΔG= −15.5 kcal/mol upon formation of heteroternary complexes through social self-sorting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…CB [8] is the most widely utilized supramolecular nanoreactor owing to its appropriate size and strong affinity for containing two or more guests homogeneously or heterogeneously. [23,24] In 1983, Mock and co-workers first reported the CB [6] catalyzed 1,3 dipolara zide-alkynec ycloaddition( AAC) reaction. [25,26] The azide andt he alkyne groups were encapsulatedi nt he cavity of CB [6],a nd the amino groups helped to stabilize the host-guestc omplex( Figure3).…”
Section: Cucurbit[n]urils As Nanoreactorsmentioning
confidence: 99%
“…CB [8] is the most widely utilized supramolecular nanoreactor owing to its appropriate size and strong affinity for containing two or more guests homogeneously or heterogeneously. [23,24] In 1983, Mock and co-workers first reported the CB [6] catalyzed 1,3 dipolara zide-alkynec ycloaddition( AAC) reaction. [25,26] The azide andt he alkyne groups were encapsulatedi nt he cavity of CB [6],a nd the amino groups helped to stabilize the host-guestc omplex( Figure3).…”
Section: Cucurbit[n]urils As Nanoreactorsmentioning
confidence: 99%
“…5d, e and S22 †), exhibiting an enhanced uorescence at 430 nm and a blue-shi of 40 nm compared to TPE-COOH due to restricted intramolecular rotation. 56,57 The successful incorporation of TPE-COOH is probably due to the polar-p interaction 58,59 between -C 6 F 5 from the host particle and phenyl from the TPE guest (Fig. 5f).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] We also demonstrated that this benzyl-imidazolium motif could be simultaneously bound with a perfluorophenyl moiety forming strong polar-π interactions within CB [8] mediated hydrogels. 24 Similarly, Zhang et al demonstrated that an inclusion complex formed from an ester derivative of the tripeptide Phe-Gly-Gly and CB [8] could be polymerised to form both supramolecular hydrogels and microgels. 25,26 They noted that supramolecular hydrogels formed using this approach were significantly more mechanically robust than their counterparts produced by first synthesising the polymers and then forming the CB [8] complex (a phenomenon which was suggested to be a result of the viscous polymer solution limiting CB [8] diffusion).…”
Section: Introductionmentioning
confidence: 99%